Integrating Gender Issues in Recovery and Reconstruction Planning - World Bank (World Bank, Washington, DC, 2017)
This note on integrating gender issues in recovery and reconstruction planning is the fifth in a series of guidance notes on gender issues in Disaster Risk Management (DRM) in East Asia and Pacific region. There are number of key challenges that women face in different elements of post disaster risk reconstruction and recovery. This note addresses the following bottlenecks: a) housing, land titling and property rights, b) health and post disaster violence, c) community services and infrastructure restoration, and d) poverty reduction, livelihood restoration and economic development.